THE IMPACT OF THE CANCELLATION OF INDONESIA AS HOST OF THE 2023 U-20 WORLD CUP ON THE INDONESIAN ECONOMY - Aryani, Dwi Kartika; Estu Widya Putri; Nisa Aulia; Muhammad Rafly; Putri Maulidina Fadhilah; Tiur Malasari Siregar (Lembaga Riset dan Inovasi Kreyat Center, 2023)
This journal discusses the impact of Indonesia's cancellation as the host of the FIFA U20 World Cup in 2023 on the Indonesian economy. The analysis reveals that the cancellation has had negative effects on various economic sectors, including investment, tourism, and infrastructure. Investments have decreased, economic growth has been hindered, and job opportunities have been reduced. Additionally, infrastructure projects have been left unfinished, resulting in wastage of resources. In conclusion, effective economic recovery measures are needed, such as diversifying the economy and developing alternative tourism options.